The Impact of Inflation on the Stability of the Islamic Financial System - Moh. Asep Zakariya Ansori; Yadi Janwari; Sofyan Al-Hakim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
High inflation has become a challenge for a country's economy, including the Islamic financial system. The stability of the Islamic financial system is very vulnerable to be affected by inflationary turmoil. This study aims to determine and analyse the impact of inflation on the stability of the Islamic financial system. This research uses a qualitative method with the type of library research. Data were obtained from books, scientific journals, and relevant previous research reports. The data analysis technique uses content analysis with descriptive data presentation. The results showed that inflation exerts significant pressure on the stability of the Islamic financial system through various transmission channels. Inflation increases the cost of funds, the risk of non-performing financing, investment uncertainty, and systemic risk in Islamic financial institutions. On the other hand, price stability is a prerequisite for the stability of the Islamic financial system in carrying out the intermediation function and optimal allocation of financing. Therefore, the central bank and regulators need to take macroprudential policies to reduce inflationary pressures and maintain the stability of the Islamic financial system through adequate liquidity management, setting risk-based reserves, monitoring financial leverage, and supervising innovative financial products